Meat quality of young bulls finished in a feedlot and supplemented with clove or cinnamon essential oils - Torrecilhas, Juliana Akamine [UNESP]; Ornaghi, Mariana Garcia; Passetti, Rodrigo Augusto Cortez; Mottin, Camila; Guerrero, Ana; Ramos, Tatiane Rogelio; Vital, Ana Carolina Pelaes; Sañudo, Carlos; Malheiros, Euclides Braga [UNESP]; Prado, Ivanor Nunes do (Elsevier, 2021)
Forty young crossbred bulls (10 ± 2.2 months of age; 219 ± 11.7 kg) were finished in a feedlot with one of five different treatments: CON, control (no essential oil); CLO450, clove essential oil (450 mg/kg); CLO880, clove essential oil (880 mg/kg); CIN450; cinnamon essential oil (450 mg/kg); and CIN880, cinnamon essential oil (880 mg/kg). Instrumental meat quality attributes and consumer acceptability aspects (visual and sensory) were assessed during meat ageing and display. The inclusion of clove essential oil showed (P = 0.033) a quadratic effect on lipid oxidation in meat evaluated under display conditions. Level of cinnamon essential oil affected (P < 0.05) pH, shear force, and meat colour. On the other hand, the diet had no effect (P > 0.05) on sensory or visual acceptability. Ageing (7 days) enhanced (P < 0.05) sensory acceptability attributes. Globally, the addition of essential oil in bull diets can be an alternative to reduces lipid oxidation without modifying sensory acceptability attributes.
Keywords: Antioxidant; Consumers; Natural extract; Sensory analysis